Analysis of Tuning Parameters for Compact Size Microstrip Yagi Antenna - Khairuddin, A.S. (Institute of Electrical and Electronics Engineers Inc., 2021)
Microstrip Yagi antenna has been actively developed for point-to-point communication due to its end fire radiation characteristics. In order to achieve a compact size of Yagi design with efficient performance, the structure and its tuning parameters of the design needs to be analyze and properly tuned for achieving higher gain in forward direction. This paper provides an analysis of tuning parameter for microstrip Yagi antenna design which operates at resonant frequency of 2.60 GHz using CST simulation tools. The technique achieved impedance bandwidth of 0.27 GHz and a good return loss level. The antenna achieved directional radiation with gain of 6.51 dBi. In this paper, the critical design parameters of the proposed antenna are analyzed to characterize the antenna performance accordingly. Â© 2021 IEEE.